ANALISIS PENGENDALIAN KUALITAS DENGAN METODE TATISTICAL PROCESS CONTROL (SPC) DALAM UPAYA MENGURANGI KECACATAN PRODUK ROTI BAKEROLD CABANG LUBANG BUAYA JAKARTA TIMUR - Jenji Gunaedi Argo; Heni Nastiti; Rosali Colia Sembiring (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to control the quality of Bakerold bakery products in Lubang Buaya, East Jakarta by analyzing the overall amount of bread produced and the amount of bread damaged at a certain period of time using the Statistical Process Control (SPC) method, namely (check sheet, histogram, pareto diagram, cause and effect diagram and control chart) so as to determine the factors that cause disability and prevention carried out. The results of the analysis control chart show that the amount of production inspected in February 2022 was 8,724 pcs, the amount of damage was 137 pcs. The supervisory limit is UCL 0.0359, LCL is 0 because it concerns the product, the smallest value is 0. The results showed that there were 5 points of abnormal behavior that were outside the quality control limit or Upper Control Limit (UCL), the cause of deviations in the quality of Bakerold bread was caused by dough not rising and burnt caused by 4 factors, namely, humans, machines, materials and methods. The solution is done through monitoring work and urging employees to be more thorough in working, coordinating between departments and making written work guidelines, and conducting briefings and evaluations to employees regularly to reduce the occurrence of errors and evaluating employees regularly to reduce the occurrence of errors